1999
DOI: 10.1002/(sici)1097-0142(19991015)86:8<1544::aid-cncr22>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian dysplasia in prophylactic oophorectomy specimens

Abstract: Ovaries removed by prophylactic oophorectomy examined in their entirety often reveal ovarian dysplasia and occasionally ovarian carcinoma. The new morphometric method used was highly discriminatory in the evaluation of nuclear texture. Ovarian dysplasia in women with risk factors for ovarian carcinoma is significant in early ovarian carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…Examples of these morphologic changes are shown in Figure 1B. Consistent with several previous investigations,12–15 morphologic changes are present in ovarian tissue samples from high‐risk populations with BRCA1/2 or MLH1 mutations or a family history of breast and ovarian carcinoma. However, we have made no attempt to compare these with ovarian specimens from the normal‐risk population, because an insufficient number are available for study.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Examples of these morphologic changes are shown in Figure 1B. Consistent with several previous investigations,12–15 morphologic changes are present in ovarian tissue samples from high‐risk populations with BRCA1/2 or MLH1 mutations or a family history of breast and ovarian carcinoma. However, we have made no attempt to compare these with ovarian specimens from the normal‐risk population, because an insufficient number are available for study.…”
Section: Resultssupporting
confidence: 87%
“…Recently, women from high‐risk breast and ovarian carcinoma families, often BRCA1 and BRCA2 carriers, elected prophylactic oophorectomy as a preventive approach 10, 11. Ovarian tissue specimens from women with a high risk for breast and ovarian carcinoma but without clinical diagnoses or symptoms have provided the means to investigate ovarian preneoplastic changes 12–15. Several studies have found microscopic benign‐to‐malignant morphologic changes in ovarian specimens,14–16 and others have suggested the existence of preneoplastic phenotypes in the cells prepared from ovaries in cancer‐prone women 13, 15.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The macroscopic appearance of the removed ovaries usually is unremarkable. Thorough histologic examination of entirely submitted ovaries, however, may yield a number of structural changes, as reported in microscopic descriptions4–8 and computerized image analyses 9–12. For some of these changes, the terms ovarian dysplasia or ovarian intraepithelial neoplasia have been proposed,4, 5 suggesting that they may represent precursor lesions of invasive ovarian carcinoma.…”
mentioning
confidence: 99%
“…The frequencies of several types of morphologic alterations, including epithelial pseudostratification, papillomatosis, cortical invagination, inclusion cysts, and stromal hyperplasia, were shown to be significantly higher in the cancer‐prone ovaries than in control tissues. However, of two similar studies, one failed to document morphologic differences in ovaries from BRCA heterozygotes compared with control ovarian tissues,16 whereas another found ovarian dysplasia to be more common in ovaries from BRCA heterozygotes than from controls 17…”
mentioning
confidence: 99%